The Dudleys, Sir Christopher Hatton and the Justices of Elizabethan Warwickshire. (April 2014) - E, C
Abstract : Robert Dudley, Earl of Leicester and Ambrose Dudley, Earl of Warwick, were the most important magnates in Warwickshire for the first thirty years of the reign of Elizabeth I. During the 1570s, Christopher Hatton rose from apparent obscurity to become one of Elizabeth's most important councillors and was appointed lord chancellor in 1587. This paper suggests that Hatton's rise during the 1570s was partially a response to the activities of the Dudleys and that Hatton's previously neglected connections to Warwickshire made him well-placed to act as an alternative source of influence in the county. It analyses the Warwickshire Commission of the Peace as background to the political narrative of this period and presents the suppression of the prophesyings in 1576 and the political marginalisation of the Catholic Throckmorton kinship network as consequences of the influence of Hatton and the Dudleys respectively.